Oral and systemic changes in Langerhans Cell Histiocytosis in a pediatric patient: Case report (Research, Society and Development, 2021)
Langerhans Cell Histiocytosis (LCH) is a disorder associated with the proliferation of Langerhans cells. Due to its infiltrative nature, LCH can involve organs such as the skin, the ganglia, the lung and the liver. It is estimated that its incidence is approximately 5 to 10 cases in a million per year, mainly in children under 15 years old, with a predominance in males, in the proportion of 2: 1 and its pathogenesis remains unknown. The objective of this study was to describe the systemic and oral manifestations of LCH in a child, highlighting the importance of the dental surgeon in the early diagnosis of oral lesions in primary care. For the description of the clinical case, the information was obtained by consulting the patient's medical record at Hospital University Onofre Lopes - HUOL. Male patient, 4 months old, presented lesions in the oral cavity in the lower, upper alveolar ridge and hard palate, exophytic formed by erythroplastic and leukoplastic regions not removed during scraping, with abdominal distension, normotensive fontanelle, presence of parietal cephalic “nodule”, jaundice, choluria, fecal hypocholia and hyperemic genitals. We concluded that the child had a clinical condition compatible with LCH. This work also showed the importance of the dentist, especially in Primary Health Care, for the correct diagnosis of systemic diseases, with oral manifestations, as well as his responsibility in ordering care in the search for comprehensive care.